The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1143/jjap.30.3219
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Ultraviolet Laser-Induced Surface Alteration of SiO2

Abstract: Intense vacuum ultraviolet laser radiation is generated from rare gas excimer lasers. 9.8 eV photons from an argon excimer laser change surfaces of SiO2 to silicon. The reaction proceeds without the aid of reactive gas or solution and is thus called the “superdry process”. 9.8 eV photons create excitons via an efficient one-photon absorption process, and then these high-density excitons induce bond-breaking between Si and O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The intermediate shank part has an oxygen-poor stoichiometry (Si 2 O) since the oxygen atoms were taken to the top part of the pipette during the fabrication process [16]. It is known that the oxygen-poor stoichiometry in glass can be produced with KrF excimer laser [17], Ar 2 excimer laser [18], and synchrotron radiation [19]. The puller used in this study can produce the temperature more than the melting temperature of boron silicate.…”
Section: Resultsmentioning
confidence: 99%
“…The intermediate shank part has an oxygen-poor stoichiometry (Si 2 O) since the oxygen atoms were taken to the top part of the pipette during the fabrication process [16]. It is known that the oxygen-poor stoichiometry in glass can be produced with KrF excimer laser [17], Ar 2 excimer laser [18], and synchrotron radiation [19]. The puller used in this study can produce the temperature more than the melting temperature of boron silicate.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the Si 2p spectrum in Figure b, the polysilole siloxane thin films fabricated from 0.1 wt % precursor solution showed two prominent peaks, where the former peak was due to the Si atoms in the thin films and the latter to the Si atoms of the silicon substrate, owing to its relatively low thickness. Because the binding energy of the Si 2p electrons from the silicon substrate -bulk silicon- is 99.3 eV, the latter peak was calibrated to 99.3 eV and, hence, positioned the former peak to 102.8 eV without further consideration. The peak at 99.9 eV might arise from a Si atom at an imperfect oxidation state of +1, in the shallow native-oxide layer between the polysilole siloxane film and Si wafer .…”
Section: Resultsmentioning
confidence: 99%
“…Kurosawa et al have observed that argon (9.8 eV, 126.5 nm) excimer laser irradiation transforms the surfaces of the SiO 2 to Si (i.e., the 9.8 eV induces desorption and Si precipitation in the surface layers of the SiO 2 ) [66]. Kurosawa et al have observed that argon (9.8 eV, 126.5 nm) excimer laser irradiation transforms the surfaces of the SiO 2 to Si (i.e., the 9.8 eV induces desorption and Si precipitation in the surface layers of the SiO 2 ) [66].…”
Section: Opticalmentioning
confidence: 99%
“…Thus, the VUV photons from the argon laser are capable of causing surface alteration [66]. A high density of excitons can stimulate breaking of Si-O bonds, which can result in Si precipitation and oxygen desorption on the SiO 2 surface.…”
Section: Opticalmentioning
confidence: 99%